The Strategy to Control the Morphology of ZnO Nanostructure UV Sensor - Humayun, Q; Hashim, U; Ruzaidi, C M; Foo, Kai Loong (IOP conference series. Materials Science and Engineering, 2015)
The control morphology of ZnO nanostructures at specific area of electrodes by implemented a cost effective fabrication process, is extremely a challenging task. Rapid sensing, fast response and fast detection capability of the electronics devices is nowadays hot subject of keen interest. Our research is one of the successful attempts to achieve the desired goal at certain levels. Therefore in the current research article the ZnO thin film and ZnO nanorods were selectively deposited by low cost sol-gel and hydrothermal growth process at the selective area of microgap electrodes spacing and further the comparative study of ZnO thin film and ZnO nanorods were conducted electrically, for ultraviolet (UV) sensing application. On exposure to ultraviolet (UV) light the current gains, response recovery times, repeatability, of the ZnO nanorods compared with ZnO thin film was improved probably due to the role of large surface area covered by the deposited nanostructures, and the most important is the bridging nanorods at the microgap electrodes tips. All the characterization including, surface, electrical and structural of the deposited nanostructures were completed by using SEM, sourcemeter and XRD respectively.